The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1186/s13017-023-00530-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of initial lactate levels and red blood cell transfusion strategy with outcomes after severe trauma: a post hoc analysis of the RESTRIC trial

Yoshinori Kosaki,
Takashi Hongo,
Mineji Hayakawa
et al.

Abstract: Background The appropriateness of a restrictive transfusion strategy for those with active bleeding after traumatic injury remains uncertain. Given the association between tissue hypoxia and lactate levels, we hypothesized that the optimal transfusion strategy may differ based on lactate levels. This post hoc analysis of the RESTRIC trial sought to investigate the association between transfusion strategies and patient outcomes based on initial lactate levels. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This may be because lactate, as a biomarker of inadequate tissue perfusion, is highly correlated with the overall burden of trauma in PT patients. In addition, the included patients presented with a very high ISS compared to other studies that investigated the role of lactate in PT [ 1 , 7 , 16 , 19 ]. However, the present study demonstrated that serum LDH levels exhibited a correlation with the occurrence of concomitant chest injuries among patients afflicted with PT.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because lactate, as a biomarker of inadequate tissue perfusion, is highly correlated with the overall burden of trauma in PT patients. In addition, the included patients presented with a very high ISS compared to other studies that investigated the role of lactate in PT [ 1 , 7 , 16 , 19 ]. However, the present study demonstrated that serum LDH levels exhibited a correlation with the occurrence of concomitant chest injuries among patients afflicted with PT.…”
Section: Discussionmentioning
confidence: 99%